COMPARATIVE ANALYSIS OF HUGO CH VES’S SOCIAL POLICY (2007–2011) - Tatyana Rusakova (Сравнительная политика)
Abstract: During the years of 2007–2011 Venezuela’s government continued the battle with poverty and unemployment, growing nutritional and housing deficit. Also some measures have been adopted to make education and health service more accessible for the population of the country. Thus the government activity in the sphere of social politics has had fragmented character and has been recepient-oriented to achieve shortterm effects to win presidential elections in October 2012.